Colour photographs for screening in neovascular age-related macular degeneration: are they necessary? - Hibbs, S; Smith, A; Chow, L; Downes, S (2011)
AIMS: To investigate whether optical coherence tomography (OCT) with associated infra-red images provide enough information to determine treatment decisions in the management of neovascular age-related macular degeneration (nAMD), or whether retinal colour photography is also necessary. METHODS: In all, 87 OCT scans of 82 eyes with nAMD undergoing monitoring post ranibizumab treatment were taken using the Zeiss Stratus (Carl Zeiss Meditec, Jena, Germany; n=87) together with their corresponding infra-red images. Fundus colour photographs were also taken. These images were reviewed by an experienced assessor, and a ranibizumab treatment decision was made during a multidisciplinary team retinal image review meeting. RESULTS: In all, 30 OCT scans (34.5%) showed intraretinal or subretinal oedema. A total of 24 colour photographs (19.5%) demonstrated retinal haemorrhage. Corresponding OCT infra-red images gave poor sensitivity in detecting haemorrhages (0.176). In 16.7% of decisions to treat, haemorrhage alone was the deciding factor. Signs of disease activity seen only on colour photography were the deciding factor in clinical decisions for 8% of scans assessed. CONCLUSIONS: The presence or increase of intra-retinal oedema is an important sign of activity triggering ranibizumab retreatment, but some eyes show signs of retinal haemorrhage without coexisting oedema. These haemorrhages are often only seen on either colour imaging or fundoscopy and are unclear or invisible on OCT scans and infra-red images. Therefore, although retinal colour photography creates additional expense, it is indispensable for making informed retreatment decisions, if patients are monitored using retinal imaging alone.